Immunoinformatics‐aided identification of T cell and B cell epitopes in the surface glycoprotein of 2019‐nCoV. Issue 5 (3rd March 2020) - Baruah, Vargab; Bose, Sujoy
Abstract: The 2019 novel coronavirus (2019‐nCoV) outbreak has caused a large number of deaths with thousands of confirmed cases worldwide, especially in East Asia. This study took an immunoinformatics approach to identify significant cytotoxic T lymphocyte (CTL) and B cell epitopes in the 2019‐nCoV surface glycoprotein. Also, interactions between identified CTL epitopes and their corresponding major histocompatibility complex (MHC) class I supertype representatives prevalent in China were studied by molecular dynamics simulations. We identified five CTL epitopes, three sequential B cell epitopes and five discontinuous B cell epitopes in the viral surface glycoprotein. Also, during simulations, the CTL epitopes were observed to be binding MHC class I peptide‐binding grooves via multiple contacts, with continuous hydrogen bonds and salt bridge anchors, indicating their potential in generating immune responses. Some of these identified epitopes can be potential candidates for the development of 2019‐nCoV vaccines. Highlights: Five CTL epitopes and eight B cell epitopes were computationally identified. Epitope‐MHC‐I complexes were studied by molecular dynamics simulation. Persistent H‐bonds and salt bridges were observed between epitopes and MHC‐I. The identified epitopes can be a promising foundation for vaccine development.